Crash Performance of Double Hat Column Subjected to Compression Loading - Salwani, Mohd Salleh; Mohamad Hisyam, K. (IOP Publishing, 2020)
There are many types of structure designed to act like an energy absorber. Energy absorber is the one that responsible to absorb energy during crashes. An energy absorber is a system that converts, totally or partially, kinetic energy into another form of energy. Energy converted is either reversible or irreversible. One of the examples of the most important structure to absorb energy is the crash box. Crash box can be found in many shapes, and double hat column is the common one. The objective of this study is to study the effect of heat treatment and notch on the performance of the double hat column structure. The results of different specimens were compared in terms of tensile strength and also energy absorbed. It was found that the tensile strength and energy absorbed was slightly higher for specimens that were quenched in lower temperature and longer time and for notching distance of 20mm.